PRINSIP MULTIMAKNA DALAM PENDIDIKAN PASRAMAN NON-FORMAL DI NUSA TENGGARA BARAT - Astrina, Wayan Ayumita (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2026)
Non-formal pasraman institutions in West Nusa Tenggara likewise reflect efforts to optimize their contribution to improving student competencies by strengthening the actualization of multiple meanings principles in their learning processes. This study aims to analyze more deeply the application of multiple meanings principles in pasraman education using participant and non-participant observation, unstructured interviews, and documentation studies. The findings show that learning programs such as upakara training, Balinese dance, dharmagita, Balinese script, and yoga emphasize the cultivation of local wisdom, the empowerment of individual potential, character and personality formation, and the development of life skills. Pasraman functions not only as a place to learn religious teachings but also as a space for character building and self-development rooted in Hindu values and local wisdom. Education in pasraman offers holistic learning that integrates intellectual, emotional, spiritual, social, and cultural dimensions.